Needs Analysis of Bioassay Course Teaching Materials Based on Rhizophoraceae Phytochemical Research to Strengthen Science Process Skills of Biology Education Students - indriaty; Sri Jayanthi; Muhammad Khalil; Hadi Wibowo Atmaja; Ayu Wahyuni (Jurnal Penelitian Pendidikan IPA, 2025)
The Bioassay course plays an important role in developing students’ science process skills. However, its implementation still lacks structured and contextual learning resources that integrate local research-based content. This study aims to analyze students’ needs for Bioassay learning resources as a basis for developing research-based textbooks integrating local Rhizophoraceae phytochemical studies. The research employed a descriptive quantitative method involving sixth-semester Biology Education students who had completed the course. Data were collected through structured questionnaires and interviews, then analyzed descriptively using percentages to identify students’ needs for Bioassay teaching materials. The results revealed that students predominantly utilized journal articles (100%), lecturer slides (95%), and online textbooks (50%) as their primary sources of learning. However, these materials were fragmented and lacked contextual relevance to Bioassay learning. Although 70% of students showed high interest, 50% still experienced difficulties in understanding concepts and applying bioassay techniques appropriately. Furthermore, 85% of students expressed the need for systematic Bioassay textbooks, and 90% supported the development of textbooks based on local mangrove research. The findings indicate that students have a clear need for structured and contextual Bioassay learning resources that integrate local studies on the Rhizophoraceae mangrove family to enhance conceptual understanding and scientific process skills